Crystal structure of catena-poly[(ethylenediamine-κ2 N,N′)-μ-tetraoxomolybdato(VI) zinc(II)], C2H8MoN2O4Zn - Zhuo Xin (Zeitschrift für Kristallographie - New Crystal Structures)
C2H8MoN2O4Zn, monoclinic, P21/c (no. 4), a = 10.3133(6) Å, b = 9.6996(5) Å, c = 7.2740(4) Å, β = 106.088(1)°, V = 699.16(7) Å3, Z = 4, Rgt (F) = 0.0191, wRref (F 2) = 0.0512, T = 296(2) K.